Root proliferation in native perennial grasses of arid Patagonia, Argentina - Torres, Yanina Alejandra (2014)
Pappophorum vaginatum is the most abundant C4 perennial grass desirable to livestock in rangelands of northeastern Patagonia, Argentina. We hypothesized that (1) defoliation reduce net primary productivity, and root length density and weight in the native species, and (2) root net primary productivity, and root length density and weight, are greater in P. vaginatum than in the other, less desirable, native species (i.e., Aristida spegazzinii, A. subulata and Sporobolus cryptandrus). Plants of all species were either exposed or not to a severe defoliation twice a year during two growing seasons. Root proliferation was measured using the cylinder method. Cylindrical, iron structures, wrapped up using nylon mesh, were buried diagonally from the periphery to the center on individual plants. These structures, initially filled with soil without any organic residue, were dug up from the soil on 25 April 2008, after two successive defoliations in mid-spring 2007. During the second growing season (2008–2009), cylinders were destructively harvested on 4 April 2009, after one or two defoliations in mid-and/or late-spring, respectively. Roots grown into the cylinders were obtained after washing the soil manually. Defoliation during two successive years did reduce the study variables only after plants of all species were defoliated twice, which supported the first hypothesis. The greater root net primary productivity, root length density and weight in P. vaginatum than in the other native species, in support of the second hypothesis, could help to explain its greater abundance in rangelands of Argentina.